Edwards Wasp Moth, Lymire edwardsii (Grote) (Insecta: Lepidoptera: Arctiidae: Ctenuchinae) - Dale H. Habeck; Frank W. Mead (EDIS, 2004)
The caterpillars of Edwards wasp moth frequently cause extensive injury to Ficus trees. Bratley (1929) called it the rubber tree caterpillar because of its injury to rubber trees (Ficus spp.). The immature stages were described by Edwards (1887) and Dyar (1890). Genung (1959) published a comprehensive study on the moth's biology and its control in the Lake Worth, Florida area. This document is EENY-182 (originally published as DPI Entomology Circular 234), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2000.